2000
DOI: 10.1128/aem.66.5.2133-2138.2000
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Evaluation of a Novel Bifunctional N -Carbamylase– d -Hydantoinase Fusion Enzyme

Abstract: gene from Bacillus thermocatenulatus GH2 was also fused with the N-carbamylase gene at its N terminus. The resulting enzyme (CAB-HYD1) was bifunctional as expected and showed better performance than the CAB-HYD fusion enzyme. The conversion of hydantoin derivatives to corresponding amino acids by the fusion enzymes was much higher than that by the separately expressed enzymes, and comparable to that by the coexpressed enzymes. Thus, the fusion enzyme might be useful as a potential biocatalyst for the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…This is the same as for the BTS1-ERG20 fusion gene. Such a proximity effect and substrate channeling for fusion enzymes have been reported to increase the overall catalytic activity of the reaction in vitro (11,15,17,33). We demonstrated that the use of bifunctional fusion genes was also highly effective for metabolic engineering.…”
Section: Discussionmentioning
confidence: 78%
“…This is the same as for the BTS1-ERG20 fusion gene. Such a proximity effect and substrate channeling for fusion enzymes have been reported to increase the overall catalytic activity of the reaction in vitro (11,15,17,33). We demonstrated that the use of bifunctional fusion genes was also highly effective for metabolic engineering.…”
Section: Discussionmentioning
confidence: 78%
“…in the presence of plasmid pMCS69 was therefore likely to be due to the inefficient fusion of PhaA to PhaB. This was not unexpected as both PhaA and PhaB enzymes function catalytically as homo-tetramers (Davis et al, 1987;Ploux et al, 1988) so fusions of these could reduce the activity by interfering with quaternary structures (Carlsson et al, 1996;Kim et al, 2000).…”
Section: Discussionmentioning
confidence: 88%
“…It is generally recognized that closer spatial distance between the fused proteins affects their folding, function, and expression. Flexible linkers are typically incorporated in cases where the fused domains require a certain degree of movement or interaction (Kim et al, 2000;Blazyk and Lippard, 2004;Jiang et al, 2005;Wang et al, 2007;Lu and Feng, 2008). Most commonly used flexible linker sequences primarily consist of Gly and Ser residues ("GS" linker) (Huston et al, 1988;Kavoosi et al, 2007;Hölsch and Weuster-Botz, 2010).…”
Section: Discussionmentioning
confidence: 99%